2011
DOI: 10.1200/jco.2011.29.4_suppl.315
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of lapatinib and capecitabine in first-line treatment of metastatic pancreatic cancer (ICORG 08- 39).

Abstract: 315 Background: The combination of capecitabine plus erlotinib in gemcitabine-refractory advanced pancreatic cancer patients has proved beneficial in terms of median survival duration, objective radiological response rate and decrease in tumour marker levels from baseline. In the phase I study of capecitabine and lapatinib carried out in advanced solid tumors, the optimal tolerated regimen was determined to be lapatinib 1,250 mg plus capecitabine 2,000 mg/m2/day. At these dose levels, the combination was well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A phase II trial of lapatinib and gemcitabine revealed that this combination may not be effective in pancreatic cancer [34]. Phase II clinical trials investigating the combination of lapatinib and capecitabine for second-line treatment of metastatic pancreatic cancer are currently on-going (ClinicalTrials.gov, NCT00881621) [35]; however, it has been found that this combination does not improve the overall survival in the first-line treatment of advanced pancreatic cancer patients [36]. Many studies show that EGFR is over-expressed in pancreatic cancer [12], our IHC results are in agreement, whereby EGFR was over-expressed in 44 % of pancreatic tumours with significant correlation to adenocarcinoma tumour type (p0 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…A phase II trial of lapatinib and gemcitabine revealed that this combination may not be effective in pancreatic cancer [34]. Phase II clinical trials investigating the combination of lapatinib and capecitabine for second-line treatment of metastatic pancreatic cancer are currently on-going (ClinicalTrials.gov, NCT00881621) [35]; however, it has been found that this combination does not improve the overall survival in the first-line treatment of advanced pancreatic cancer patients [36]. Many studies show that EGFR is over-expressed in pancreatic cancer [12], our IHC results are in agreement, whereby EGFR was over-expressed in 44 % of pancreatic tumours with significant correlation to adenocarcinoma tumour type (p0 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…Median PFS in our trial was 65 days with an OS of 6.9 month, which is similar to single-agent capecitabine ( Cartwright et al , 2002 ). In a recent study, published in abstract form ( McDermott et al , 2011 ) capecitabine in combination with lapatinib, a small molecule, tyrosine kinase inhibitor of epidermal growth factor receptor and HER2 showed disappointing antitumour activity with an OS of 4 months. Our study showed an median OS of 6.9 months, but taken together capecitabine in combination with anti-HER2 therapy does not seem to significantly improve treatment results in comparison with historical capecitabine monotherapy (mean OS 6.0 months; Cartwright et al , 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, preliminary results of a single arm phase II trial evaluating the combination of capecitabine and lapatinib as firstline treatment in advanced pancreatic cancer have been presented. Survival of 6 months was not reached in 7 of the 9 enrolled patients, and none of them obtained objective responses (McDermott et al, 2011). This data led to the premature termination of the study.…”
Section: Erlotinib Is An Oral Tyrosine Kinase Inhibitor [Tki] Againstmentioning
confidence: 99%